Efetividade de intervenções em creches públicas pautadas na educação alimentar e nutricional com diferentes abordagens na promoção da alimentação complementar saudável - Naiara Abrantes Candido (2016)
Introduction: The eating habits in the early years of life are an important milestone in the formation of healthy habits. It is essential that everyone involved in the care of children receive guidance on breastfeeding and complementary feeding. Objective: To investigate the effectiveness of different approaches of nutritional intervention on knowledge, beliefs, attitudes and intentions of caregivers of children ages 4 to 24 months of child day care municipal centers in Nova Lima / Minas Gerais. Materials and Methods: The study was conducted as a non-randomized controlled intervention with education professionals and parents of children enrolled in nursery I and II of child day care municipal centers. The participants were divided into two groups: control (GC) - Standard food and nutrition education guidance through written guidelines; and intervention (GI) that in addition to receiving the GC information, participated in four bimonthly meetings about complementary healthy feeding. It was used as basis for actions, institutional material as the Food Guide for Children Under Two Years and Primary Care Notebooks. In both groups was evaluated before and after the educational activities (average duration: 8 months), the change in the professionals' knowledge on the subject and the change in beliefs, attitudes and parental intentions through specific questionnaires. Data were analyzed using descriptive statistics and application of the Kolmogorov-Smirnov test, Mann-Whitney, chi-square, Fisher's exact, McNemar, Student t, Wilcoxon, Spearman correlation and Ancova at a level of 5% significance. Results: The study included 90 professionals (GC: 50 and GI: 40) and 169 parents of children GC:97 e GI:72). After the interventions, there was a significant increase in the average of right answers of the professionals in GI (12,2 (11.6 - 12.7) vs 10.7 (10.2 - 11.2) in GC; p = 0,001 and improvement among parents of GI in relation of beliefs (soups and broths do not nourish the child: p < 0.001), attitudes (offer meat from the sixth month p = 0.008) and intentions (not offer soups and broths: p = 0.001; provide vegetable: p = 0.006). Conclusion: The most intense nutritional intervention provided an significantly greater effect on the evaluated parameters, indicating the importance of its application in child care services. Food and nutrition education geared to infants caregivers may favor a more appropriate nutrition and adoption of good habits among children from the earliest stages of life with possible positive impact on health in future.